Методика экспериментального исследования методов управления трафиком в сети - Евсеева, О. Ю. (Проблеми телекомунікацій, 2011)
The basic problems and methodology of experimental study of traffic control methods in telecommunication network with using equipment manufactured by Cisco Systems are offered.
Keywords: лабораторный эксперимент; трафик; ТКС